'I like my job but I don't feel we are getting a fair deal' - USDAW leaflet, 1980 (1980)
1980 1960-2000 "'I like my job but I don't feel we are getting a fair deal' - USDAW leaflet, 1980" [EP0165], 1980 Recruitment leaflet for women workers from the Union of Shop, Distributive and Allied Workers.